An Augmented Reality Application for the Community Learning about the Risk of Earthquake in a Multi-storey Building Area - Pamenang, Muhammad Unggul; Basuki, Achmad; Sigit, Riyanto (Politeknik Elektronika Negeri Surabaya (PENS), 2017)
The earthquake comes with great risks, especially in urban areas where many multi-storey buildings exist. These risks have not been understood well yet by the people of the urban area. Socialization, simulation, and learning media need to be provided continuously to improve people awareness on the importance of knowledge about the earthquake risks. An interesting learning media is not only contain informations but also a 3D animation and an interaction with the user. For a more immersive interaction, this application is equipped with augmented reality technology that gives more real visual representation like the actual condition. The evaluation result shows that 82% respondent appreciates this application, at first common users do not know the risk of earthquakes on multi-storey building, with this application users can understand the importance of earthquake risk in buildings.